Mission Motivation and Public Sector Performance: Experimental Evidence from Pakistan - Khan, Muhammad Yasir (American Economic Review, 2025)
This paper studies, through a randomized field experiment involving community health workers in Pakistan, if public sector organizations can improve worker performance by investing in their mission motivation. The findings reveal that training aimed at strengthening mission motivation improves workers' performance in their core responsibility of monthly household visits, as well as in multiple tasks performed during and outside these visits. This holistic improvement in performance leads to improved health outcomes for children in the communities served by these workers. These results highlight the importance of promoting organizational missions as a strategy to improve public sector performance in low-income countries. (JEL C93, I11, J13, J24, L31, M53, O12)